Effect of eggshell temperatures on hatching performance, egg production, and bone morphology of laying hens - Kamanli, Serdar; Yalcin, Zisan Servet; Tasdemir, Ahmet Nuri; Tarim, Bulent; Tulek, Engin; Aygoren, Huseyin; Bozkurt, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2021)
The present study aims to evaluate the effect of lower or higher eggshell temperatures from days 7 to 21 on hatching performance, bone and blood parameters, and egg production along with the age of laying chickens. A total of 3150 eggs obtained from a white egg-type breeder were divided randomly into 3 groups of 1050 eggs. From 7 to 21 days, eggs were incubated at one of three eggshell temperatures: Control (IC) 37.5 degrees C, low (IL) 36.9 degrees C, and high (IH) 38.5 degrees C. At hatch, chicks were weighed, and blood was collected to measure total Ca, inorganic P, and ALP level weights, dimensions, and ash contents of femur, humerus, and tibia were obtained. A total of 240 chicks from each incubation temperature were reared up to 58 weeks. The results showed that hatchability was similar among the eggshell temperature groups. The IL chicks had the heaviest chick weight and yolk free chick weight. The IH group had reduced chick weight compared to IL and IC but increased lengths of tibia and humerus, ash contents of tibia and femur, and blood Ca levels at the day of the hatch. Laying hens from the IH group had impaired body weight during the laying cycle. At 58 weeks, there was no effect of eggshell temperature on egg production, bone length, and width. IH hens had lower tibia ash and serum Ca but higher P and ALP levels compared to IL and IC groups. However, bone mineral content and mineral density were similar for hens from different eggshell temperature groups. In conclusion, it appeared that although chicks from the IH group had reduced chick weight, they had improved bone morphology and ash content of bones compared to IC and IL at hatch. However, IH hens could not maintain the higher ash content during the grow-out and laying periods. The results indicate that the positive effect of IH incubation temperature on bone morphological measurements and ash content of tibia would not be long term.
Keywords: Incubation temperature; laying chick; laying hen; bone; egg production